Review of heat exposure equipment and in-situ characterisation techniques for intumescent coatings. (May 2021) - Dreyer, Jochen A.H.; Weinell, Claus Erik; Dam-Johansen, Kim; Kiil, Søren
Abstract: The performance of commercial intumescent coatings is assessed by industrial norms and standards with clearly defined experimental conditions. In contrast, academic research on intumescent coatings is much more diverse and there are no clear guidelines on how such coatings should be characterised. Some researchers transfer the conditions defined in the industrial standards to laboratory-scale setups while others rely on cone calorimeters or Bunsen burners. This might not be an issue when comparing different coating formulations within one study. However, it significantly complicates the comparison of coatings characterised with different experimental approaches and usually provides little insight into the coating performance under industrial fire test conditions. This review article gives an overview over different experimental approaches reported in the academic literature for the performance evaluation of intumescent coatings. The heating conditions in these different groups of setups, ranging from furnaces and ovens over radiative heaters to impinging flames, are elaborated in a tutorial style fashion. Besides the sample heating, in-situ characterisation techniques, such as measurements of char expansion, temperature, and mechanical strength will be discussed. The aim is to aid researchers in evaluating literature reports as well as stimulate the development of new and the optimisation of existing experimental approaches. Highlights: Common industrial standards for testing intumescent coatings are summarised. Fundamentals of different modes of heating are explained. The different experimental techniques used in the academic literature are reviewed. The capabilities and limitations of each experimental technique are discussed. Recommendations for future development of experimental techniques are made.